The power of cultural resource bricolage: Driving market performance through customer-culture theory - Putra, Febrianur Ibnu Fitroh Sukono; Panjaitan, Roymon; Fatmawati, Elia Resha; Rumanti, Seline Widi (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
Small and Medium Enterprises (SMEs) that produce traditional products face a dilemma between preserving cultural authenticity and innovating. This study aims to explore the mediating role of Cultural Resource Bricolage (CRB) in enhancing Innovative Market Performance (IMP) through the Cultural Authenticity Perception (CAP). Data were collected from 356 SMEs in the traditional culinary, ethnic fashion, and ethnic jewelry sectors in Central Java, Indonesia, and analyzed using the SEM-PLS method. The results show that CRB significantly mediates the relationship between CAP and IMP, helping SMEs preserve cultural authenticity while remaining relevant in modern markets. It was found that CAP is the most significant construct in influencing outcomes, although its performance is slightly lower compared to CRB. These findings provide practical contributions by offering culture-based innovation strategies that SMEs can implement and theoretical contributions by expanding the understanding of the relationship between cultural authenticity, innovation, and market performance.